(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2025)
Procedures such as the fading out (FO) are poorly studied in interventions in the language of people with Alzheimer’s Disease (PWAD). The aim of the study was to investigate whether a progressive FO of questions would enhance the narrative of stories with visual support in PWAD. Twelve adults (aged 68 to 89) were divided into a control group (without indications of AD) and an experimental group (EG - with indications of AD). In pre- and post-test, participants narrated a story based on a sequence of four illustrated cards. During the intervention (three stages), each participant described a comic strip story with three scenes. At each stage, a progressively decreasing number of questions about each scene was posed before the participant told the story. The procedure did not significantly affect the overall word count used by participants, but improved the coherence of stories told by participants in the EG.